펨토초라식수술 후 미만층판각막염과 동반하여 발생한 중심독성각막병증 - 박세영(Se Young Park), 곽주영(Joo Young Kwag), 최진석(Jin Seok Choi), 박규홍(Kyu Hong Pak), 정성근(Sung Kun Chung), 현주(Joo Hyun) (Daihan angwa haghoi jabji, 2020)
목적: 펨토초라식수술 이후 발생한 중심독성각막병증 1예를 보고하고자 한다. 증례요약: 26세 남자 환자가 펨토초라식수술 후 2일째 미만층판각막염이 발생하였다. 스테로이드점안액을 사용하였으나 수술 후 6일째 우안의 미만층판각막염이 악화되어 절편 세척을 시행한 후 경구 스테로이드를 처방하였다. 수술 후 10일째 세극등현미경검사상 우안의 주변부 혼탁은 호전되었으나 중심부 혼탁과 기질선조가 관찰되었다. 수술 후 4주째에 시행한 우안 현성굴절검사상 +4.25 Dsph=-1.25 Dcyl Axis 80°로 원시 이행이 확인되었다. 수술 후 8주까지 항생제와 스테로이드점안액, 경구 독시사이클린을 처방했고, 미만층판각막염이 호전되고 혼탁만 남은 수술 8주 이후는 치료 없이 경과 관찰했다. 중심각막두께는 수술 후 8주째 488 μm에서 수술 후 72주째 540 μm로 회복되었으며, 우안 현성굴절검사상 +1.25 Dsph=-0.75 Dcyl Axis 85°였다. 각막중심부 혼탁도 호전되었다. 결론: 펨토초라식수술 후에 미만층판각막염과 중심독성각막병증이 병합되어 발생하는 경우도 있으므로 두 질환의 임상양상을 숙지하고 시기에 따른 적절한 치료를 할 수 있어야 한다. Purpose: To report a case of central toxic keratopathy after femtosecond laser in-situ keratomileusis (LASIK). Case summary: A 26-year-old male developed diffuse lamellar keratitis bilaterally on day 2 after femtosecond LASIK. He was applying topical steroid frequently, while also using topical antibiotics. On day 6 after LASIK, slit-lamp biomicroscopy showed a thick central corneal opacity on the right eye so a flap irrigation was performed. He was then treated with systemic methylprednisolone. A corneal epithelial crack and stromal striae were noted by slit-lamp biomicroscopy on postoperative day 10. Four weeks after LASIK, the refractive error was +4.25 Dsph = -1.25 Dcyl Axis 80°. He was treated with topical steroid, topical antibiotics, and oral doxycycline until eight weeks after LASIK. Eight weeks after LASIK, the patient was observed without treatment. The central corneal thickness recovered from 488 μm at eight weeks to 540 μm, and the refractive error was +1.25 Dsph = -0.75 Dcyl Axis 85° at postoperative 72 weeks. The central corneal opacity also recovered. Conclusions: Because femtosecond LASIK may result in a combination of diffuse lamellar keratitis and central toxic keratopathy, the clinical characteristics and natural course of both diseases should be understood and timely treatment should be available. KCI Citation Count: 0